Kompiuterinio raštingumo tyrimai Lietuvoje - Otas, Alfredas; Petrauskas, Vytautas; Telešius, Eugenijus (Information & Media, 2008)
Straipsnyje nagrinėjama Lietuvos piliečių kompiuterinio raštingumo problema. Trumpai pristatoma informacinės visuomenės plėtros Lietuvoje situacija. Pateikiama 2006 metų pabaigoje atlikto visuotinio kompiuterinio raštingumo tyrimo metodika ir analizuojami gauti rezultatai. Aptariamos kompiuterinio raštingumo situacijos kitimo tendencijos, apibendrinant trejų metų tyrimų rezultatus. Researches of computer literacy in Lithuania Alfredas Otas, Vytautas Petrauskas, Eugenijus Telešius Summary This article deals with the situation of the Information Society development in Lithuania. It reviews the researches of the general computer literacy in 2004–2006 in Lithuania. These researches reveal a rather high level of computer literacy among Lithuanian citizens. Approximately 50 percent of potentially active Lithuanian citizens who participated in the surveys claim to have achieved a good level of computer literacy. The researches aimed at providing a representative and adequate assessment of the population in terms of statistically important characteristics. The tendencies are described and recomendations regarding computer literacy level improvement are presented.